2022
DOI: 10.1038/s41467-022-28705-x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive translational reprogramming of metabolism limits the response to targeted therapy in BRAFV600 melanoma

Abstract: Despite the success of therapies targeting oncogenes in cancer, clinical outcomes are limited by residual disease that ultimately results in relapse. This residual disease is often characterized by non-genetic adaptive resistance, that in melanoma is characterised by altered metabolism. Here, we examine how targeted therapy reprograms metabolism in BRAF-mutant melanoma cells using a genome-wide RNA interference (RNAi) screen and global gene expression profiling. Using this systematic approach we demonstrate po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 60 publications
(101 reference statements)
0
12
0
Order By: Relevance
“… 44 , 45 Interestingly, some studies have indicated that UHMK1 can mediate oxaliplatin, 28 5‐fluorouracil 46 resistance in colorectal cancer, and vemurafenib resistance in melanoma. 22 Our findings might provide insights into UHMK1‐mediated drug resistance in tumors. Apoptosis and autophagy have a profound crosstalk during cancer progression; they may antagonize or assist each other.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“… 44 , 45 Interestingly, some studies have indicated that UHMK1 can mediate oxaliplatin, 28 5‐fluorouracil 46 resistance in colorectal cancer, and vemurafenib resistance in melanoma. 22 Our findings might provide insights into UHMK1‐mediated drug resistance in tumors. Apoptosis and autophagy have a profound crosstalk during cancer progression; they may antagonize or assist each other.…”
Section: Discussionmentioning
confidence: 85%
“…UHMK1 has been implicated as an attractive therapeutic target by exerting its potent oncogenic functions in different ways in many types of cancer. 20 , 21 , 22 , 23 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 40 This motivated us to explore the role and possible mechanism of action of UHMK1 in LUAD. In our study, we identified UHMK1 as significantly overexpressed in LUAD patients, leading to a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This picture is further complicated by the coexistence within the same tumor of cell populations with different bioenergetic needs and metabolic profiles. Very recent work suggests that post-transcriptional regulation of metabolic genes following BRAF inhibition plays a central role in the adaptation of BRAFV600E melanoma cells via translational reprogramming [ 310 ]. Given the central role of mTORC1 signaling in the regulation of mRNA translation, it is likely that this signaling complex may be involved in this newly discovered adaptive mechanism of resistance to targeted therapy.…”
Section: Mtor Complexes and Their Regulationmentioning
confidence: 99%
“…Reversible bidirectional switching between a proliferative cell state and a slow-cycling invasive state can promote metastasis in vivo (5). Such proliferative to invasive transition (PIT) and its reverse invasive to proliferative transition (IPT) is often governed by dynamic alterations in the local microenvironment (6), including therapyinduced adaptive cellular changes (7,8). Recent characterization of melanoma cell lines and tumor samples at a single-cell level have indicated that phenotypic heterogeneity in melanoma extends beyond the binary proliferative-invasive paradigm, and cells can dynamically acquire a spectrum of phenotypes (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%